International intercourse in the sphere of the information on social sciences - Zaveckienė, Žiedūnė (Knygotyra, 1987)
The exchange of the information on social sciences has become indispensable at present. So the international systems of information are being founded, such as “DARE”, “DEVSIS”, “EUDISED”, “ECSSID”. Since 1974 the social sciences are included in the program “UNISIST” In spite of that political barriers, the complication of the subject, different views influence the succesful intercourse in the field of information. Especially efective is the cooperation of the countries of the same social system. The International system of Information on Social Sciences “MISON” has become as an example. It unites eight socialist countries: Bulgaria, Hungary, the German Democratic Republic, Mongolia, Democratic Republic of VietNam, USSR, Czechoslovakia, Poland. The agreement for the “MISON” foundation was signed on June 8th, 1976. The Structure of “MISON” is: the Council, the Head Organ and the national organs. The council includes one member from each country. It solves the most complicated problems concerning the system. The functions of the head organ are in the charge of the Institute of scientific Information on social Sciences of the Academy of Sciences of the USSR – “INION”. “MISON” represents socialist countries in various international informational programs, councils, systems. It can solve various problems connected with social sciences and indeological work in general and in solvation of inner problems. such as the organization, theory and methods of information.